Occupy Education - Blanchard, Dana (Radical Teacher, 2013)
As I sit at my desk and begin to unpack my materials for the new school year, I come across the poster from the November 2nd General Strike in Oakland. The image is of protesters with signs and flags on top of container trucks silhouetted against the setting sun at the port of Oakland. It is an image that has come to represent the high point of the Occupy struggle in the Bay Area and served as inspiration for what has become possible in the struggle against the 1%.